Peran Ketua Kamar Dan Pengurus Organisasi Pelajar Pondok Modern (Oppm) Dalam Meningkatkan Kualitas Akhlak Serta Kedisiplinan Terhadap Santri - Arissalman Alfarisi; Pupu Mahpudin; Ujang Saefuddin Rosyid (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
This research is based on the phenomenon occurring in Islamic boarding schools (pondok pesantren), where the cultivation of morality and discipline among santri is a crucial aspect in shaping the personality of Muslims with noble character. The pesantren not only functions as an institution for transferring religious knowledge but also bears a great responsibility in instilling moral values, ethics, and discipline in the daily lives of its students. In this process, dormitory leaders and the Student Organization of Modern Islamic Boarding School (OPPM) hold a strategic role, serving not only as technical administrators in the dormitory but also as role models, supervisors, and mentors who directly interact with the students’ daily activities. The purpose of this study is to explore the role of dormitory leaders and OPPM administrators in enhancing the morality and discipline of santri, to identify supporting factors that facilitate the implementation of their duties, and to reveal the challenges encountered in the process of guidance. This study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, direct observation of santri activities, and documentation of dormitory regulations. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, resulting in findings that are systematic and comprehensive. The findings indicate that dormitory leaders play a significant role in nurturing morality through the habituation of Islamic behavior, providing advice, and conducting routine supervision. Meanwhile, OPPM administrators contribute greatly to enforcing discipline by implementing rules, organizing activity schedules, giving sanctions and rewards, and creating a collective atmosphere of discipline. Supporting factors include the full support of pesantren leaders, a religious environment, cooperation among administrators, and the high awareness of some students. On the other hand, challenges involve the diverse backgrounds of santri, differences in character, lack of self- awareness, and negative peer influence.